Computational econometrics : its impact on the development of quantitative economics - Renfro, Charles G. (Amsterdam ; IOS Press, 2004)
This publication contains a substantial amount of detail about the broad history of the development of econometric software based on the personal recollections of many people. For economists, the computer has increasingly become the primary applied research tool, and it is software that makes the computer work.
Includes bibliographical references.
Keywords: Econometrics -- Computer programs; Economics -- Statistical methods